Differentiation of malignant liver tumors by software-based perfusion quantification with dynamic contrast-enhanced ultrasound (DCEUS) - Wildner, Dane; Schellhaas, Barbara; Strack, Daniel; Görtz, Rüdiger; Pfeifer, Lukas; Fießler, Cornelia; Neurath, Markus; Strobel, Deike (Clinical Hemorheology and Microcirculation, 2019)
BACKGROUND: Enhancement patterns on contrast-enhanced ultrasound (CEUS) help to distinguish different liver tumors.
CRIS-Team WoS Importer:2019-04-16